Risk Management in Direct Procurement of Construction Services at The Klungkung Regency Government - I Gusti Ngurah Putra Wiyasa; Anak Agung Diah Parami Dewi; Anak Agung Gde Agung Yana (International Journal Labs, 2026)
Procurement of direct construction work according to Presidential Regulation Number 46 of 2025 is an election method to obtain construction service providers with a maximum contract value of IDR 400,000,000.00 (four hundred million rupiah). Meanwhile, direct procurement of construction consultancy services is an election method to obtain construction consultancy service providers with a maximum value of IDR 100,000,000.00 (one hundred million rupiah). The Klungkung Regency Government is one of the active local governments implementing direct procurement of construction services. Due to the large number of direct procurement packages being implemented, procurement actors often encounter various problems throughout the direct construction service procurement process. These challenges may lead to the emergence of risks affecting the procurement actors involved in the implementation of such projects. This study aims to identify, map, and determine risk acceptance levels, identify dominant risks, formulate mitigation strategies for dominant risks, and determine the impact of dominant risks on project cost and time. This study employed a qualitative descriptive method. Data collection methods included literature reviews, interviews, and brainstorming sessions. The study involved 30 respondents, with the results identifying 45 risks, of which 26 were classified as dominant risks. Six risks were categorized as unacceptable risks, one of which was the absence of advance payment provisions in the contract, resulting in the need for initial capital to support project operations. The proposed mitigation strategy for this risk was to establish a proportional payment scheme in the contract, such as initial installment payments or payments based on work progress. Twenty risks were categorized as undesirable risks, including technical disruptions such as network failures, internet outages, and server downtime. The mitigation strategies included preparing alternative networks, establishing backup implementation schedules, and ensuring coordination with system managers to minimize technical disruptions.